PENGARUH PROSES PRAPENUNTUTAN OLEH PENUNTUT UMUM DALAM OPTIMALISASI PENEGAKAN HUKUM DALAM TINDAK PIDANA PERTAMBANGAN DALAM KAWASAN HUTAN(Studi Kasus Putusan Nomor : 63/Pid.B/LH/2022/PN Kba) - Muhammad Aulia Akbar; Tofik Yanuar Chandra; Maryano Maryano (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Indonesia is a country known for having a wealth of natural and mineral resources, such as crude oil, coal, copper, iron ore, tin and gold. With the wealth it has, the Indonesian State carries out exploration activities for natural resources as one type of exploration activity by carrying out mining activities. However, mining activities often carried out do not comply with applicable regulations, which can cause environmental damage. Mining activities without permits are widespread in the Bangka Belitung archipelago, therefore the author will examine the law enforcement process contained therein, especially in the prosecution section carried out by law enforcement officials, namely the public prosecutor through court decision Number 63/Pid.B/LH/2022/PN Kba, The method used by the author in collecting data was normative research methods, the author found that the Public Prosecutor was inappropriate in imposing charges by applying regulations that were not in accordance with the facts of the material actions of the defendants and legal facts what was revealed at the trial, evidence, and legal evidence presented at the trial.